PREPARATION OF THEMATIC MAPS ON SOIL ZONING FOR DOMINICO VARIETY BANANA CULTIVATION USING GIS TOOLS, IN THE MILAGRO GUAYAS AREA. - Duque, Msc. Pedro Velez (South Eastern European Journal of Public Health, 2025)
This article focuses on the development of thematic maps using Geographic Information Systems (GIS) tools to determine soil types suitable for banana cultivation in the province of Milagro. This process requires information from organizations dedicated to edaphoclimatic studies. Once the data is collected, thematic maps will be created to clearly identify the zones and soil levels present in the area. Additionally, the use of Geographic Information Systems (GIS) provides a valuable tool for data-driven decision-making, enabling more precise and sustainable planning, optimizing resource allocation, and minimizing risks to improve agricultural productivity.